The way things work. Floating [videorecording (DVD)] - Zamora, Diego; Macaulay, David (Schlessinger Media, 2003)
A bridge collapses and strands a Mammoth Islander and his mammoth on a small island. A young Islander discovers the principle of buoyancy when she observes wood floating on the water, and this aids in the rescue.